Pelanggaran Hak Kedaulatan bagi Rakyat Secara Sistematis dalam Parliamentary Threshold pada Pemilu di Indonesia - Putri, Vanesa Ingka; Ayuningtyas, Vira; Mariyam, Yurike Siti; Syahida, Lubabah Shobrina (Fakultas Syariah INSURI Ponorogo, 2023)
Parliamentary threshold or parliamentary threshold is a threshold requirement for the acquisition of votes by political parties participating in the general election which aims to be able to send representatives to parliament. The existence of a parliamentary threshold is expected to provide a change to be able to accommodate all groups, but for political parties that have not been able to meet the requirements related to the parliamentary threshold, political matters for their legislative candidates will be eliminated. So this gives the impression that democracy in Indonesia has not been realized as it should be because people's sovereignty is determined by whether democracy is functioning or not. This research uses normative method. This study aims to describe how the systematic violation of people's sovereignty in the parliamentary threshold in elections in Indonesia. The results of this study are (1) People's sovereignty is the main source related to the power possessed by the state, but in this case the parliamentary threshold which is considered to be able to provide a change to be able to accommodate all groups is precisely the opposite of the concept of people's sovereignty and deprives human rights. human beings in terms of association or politics where in a democratic country the sovereignty of the people is an important element in it.